ANALYSIS OF INFORMATION AND ANALYTICAL SUPPORT OF PROJECT ACTIVITY OF PUBLIC MANAGEMENT - A. Denisova (Publishing House of the State University of Management, 2018)
The project management software in public administration has been analyzed. The basic principles and criteria for evaluating project management software have been systematized. The software evaluation rules have been derived. The list of used state information systems to support project activities in the constituent entities of the Russian Federation is highlighted Conclusions have been drawn based on a comparison of dedicated systems and the most popular project management products. Based on the formulated rules, a comparison was made of the most popular project management products, as well as some of the selected information systems, and conclusions were drawn from the comparison results.